Prevalence and drug resistance patterns of ESKAPE pathogens in Nigde, Türkiye - Salim, Mohammed A; Budak Diler, Songül; Köklü, Ramazan; Öztrük, Ali; Polat, Fikriye; Mohamed Hajhamed, Nooh; Saad Mohamed, Nouh (The Journal of Infection in Developing Countries, 2026)
Introduction: The escalating burden of antimicrobial resistance (AMR) presents a significant global health challenge. ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species), frequently exhibiting multidrug resistance (MDR), are especially alarming. This study evaluated the prevalence and antibiotic susceptibility profiles of ESKAPE infections in patients from Nigde, Türkiye. Methodology: This descriptive cross-sectional study was performed at Nigde Ömer Halisdemir University Training and Research Hospital from September 2022 to June 2024. Clinical specimens were collected and evaluated for antimicrobial susceptibility with the VITEK®2 compact system. Results: A total of 13,387 bacterial isolates were obtained from 7,438 patients. The majority of isolates were Gram-negative (9,671; 72.2%), of which 3,928 (39.6%) were ESKAPE. Gram-positive isolates accounted for 3,716 (27.8%), with 1,123 (30.2%) categorized as ESKAPE. Klebsiella pneumoniae (K. pneumoniae) was the most common Gram-negative ESKAPE pathogen (1,921; 19.9%), while Escherichia coli (E. coli) was the most frequent non-ESKAPE pathogen (4,747; 49.1%). Of the 5,051 ESKAPE isolates, 29.7% (1,501) were categorized as MDR and 30.9% (1,562) as extensively drug-resistant (XDR). MDR was widespread, with the highest prevalence observed in Enterococcus faecium (76.9%). Acinetobacter baumannii exhibited the highest prevalence of XDR isolates at 72.4%. Conclusions: This study emphasizes the substantial AMR burden linked to ESKAPE infections in Nigde, Türkiye, highlighting the necessity for effective infection management, antibiotic stewardship, and continuous research to track resistance patterns.